Exposure to elevated temperature affects the expression of PIWI‐interacting RNAs and associated transcripts in mouse testes. (29th January 2023) - Chen, Wenbin; Zhao, Zhang; Cen, Shengren; Lv, Daojun; Wu, Jun; Zhou, Xumin; Yang, Taowei; Zhao, Tianxin; Hou, Longlong; Mao, Xiangming
Abstract: Background: Exposure to heat waves could result in adverse effects on human health, especially in male testicles. PIWI‐interacting RNA (piRNA) is a novel type of small non‐coding RNA, which can notably impact mRNA turnover and preserve germline maintenance in germline cells. However, piRNA's expression status when adapting to testicular heat stress remains largely unclear. Objectives: To investigate the function and mechanisms of relevant piRNAs during testicular heat stress. Materials and methods: In this study, a mouse testicular heat stress model was constructed, and the testes were removed for piRNA‐sequencing. Bioinformatics analysis was used to discover the differential expressed piRNAs, piRNA clusters, and enriched pathways. A cell heat stress model was constructed to validate the top five upregulated piRNAs. Proliferation and apoptosis assays were utilized to validate the function of selected piRNA. Bioinformatics prediction, western blotting, and immunohistochemistry were used to illustrate the downstream mechanisms. Results: Through the bioinformatics analysis, we identified the differential expression profile and enriched pathways of piRNAs and piRNA clusters during testicular hyperthermia. Besides, piR‐020492 was proved to be upregulated in heat stress mouse testes and a germ cell model. A series of in vitro assays illustrated that an overexpression of piR‐020492 could restrain the proliferation and promote the apoptosis of mouse germ cells. Kyoto Encyclopedia of Genes and Genomes analysis of piRNA‐generating genes in the testicular heat stress model and piR‐020492 targeting genes showed that the overlap pathways are adenosine monophosphate–activated protein kinase (AMPK) and insulin pathways. Validation experiments demonstrated that the key genes of AMPK and insulin pathway exhibit differential expression after an overexpression of piR‐020492 or testicular heat stress. Discussion and conclusion: In conclusion, our findings revealed the expression profile of piRNAs in testicular heat stress and illustrated the function and mechanisms of piR‐020492 in germ cells, which could provide novel insights into the mechanism of hyperthermia‐induced testicular injury.